THE APPLICATION OF BIOMASS STOVES AMONG THE BERKAT RAMA FARMER GROUP IN BIBIOSI VILLAGE, ARSO DISTRICT, KEEROM REGENCY - Pongsapan, Allo Sarira; Allo, Rombe; Mangallo, David; Pagasis, Thomas; Palamba, Pither; Joni, Joni; Rantepulung, Selyus; Membala, Semuel Boron; Tambing, Enos; Siregar, Samuel Parlindungan; Kariongan, Yakobus; Mangopo, Dultudes; Kati, Oktavianus (LPPM Univ. Ibn Khaldun Bogor, 2024)
This community service activity aims to introduce biomass stoves to communities in need, particularly those with abundant biomass waste. The biomass stove's performance has already been evaluated through prior research conducted on campus. This community service initiative will be carried out with the Berkat Rama farmer group in Bibiosi Village, a major corn production area near Cenderawasih University in Arso District, Keerom Regency. Based on preliminary site assessments, local farmers reported significant quantities of agricultural waste, specifically corn cobs, left after harvest. This waste has not been optimally utilized by farmers and is typically disposed of by burning. Motivated by this, our community service team from the Department of Mechanical Engineering at Cenderawasih University aims to introduce corn cob-fueled biomass stoves to the local community. The Community Service Program (PKM) was met with strong enthusiasm from participants, who actively engaged in the socialization session through to its conclusion. The community expressed a desire for more frequent activities of this kind to broaden their knowledge and skills, especially regarding appropriate technology applications. The final outcome of this community service is an increase in both knowledge and skills among members of the Berkat Rama farmer group, specifically in the fabrication and operation of the introduced biomass stoves. They also received training in operational safety for biomass stoves. The acquired knowledge and skills are expected to be applied and shared with other community members and farmers in the area.